Collected papers on inner speech - Fossa, Pablo; Barros, Matías (Studies on inner speech, 2024)
"Inner Speech is an increasingly relevant object of study in psychology research. In recent decades, interest in the study of inner language has even transcended the psychological sciences and has become an interdisciplinary and transdisciplinary study phenomenon. Philosophers, anthropologists, psychologists, educators, and neuroscientists have joined efforts to learn more about this everyday experience inherent in human nature. Specifically, in psychology, the study of Inner Speech has been taken up by cognitive psychologists, cultural psychologists, developmental psychologists, clinical psychologists, and educational psychologists who have ventured into the study of this intimate experience of "talking to ourselves" in silence. This book is a compilation of work on Inner Speech that has been carried out by the research team of the Cognition & Culture Laboratory (C&C Lab) of the Institute of SocioEmotional Well-being (IBEM) of the Faculty of Psychology of the Universidad del Desarrollo, Chile, for more than a decade. Throughout this book, readers will be able to approach the phenomenon of Inner Speech both at a theoretical-conceptual level and will also be able to learn about some strategies for its empirical exploration. It's worth mentioning that the works presented in this book constitute only a personal collection of theoretical elaborations and methodological approaches to Inner Speech, and not the full spectrum of currently existing research on Inner Speech. The objective of this compilation of articles is to position our line of research and present, in an organized manner, the evolution of our exploration of the phenomenon to the international research program on Inner Speech. More than closing a stage, our mission is to show the progress that we have developed for more than a decade regarding the study of Inner Speech, hoping in this way to open new questions, dialogues and methodological challenges in the international academic community"--